2020
DOI: 10.1042/bsr20200407
|View full text |Cite
|
Sign up to set email alerts
|

The role of Rho GTPases’ substrates Rac and Cdc42 in osteoclastogenesis and relevant natural medicinal products study

Abstract: Recently, Rho GTPases substrates include Rac (Rac1 and Rac2) and Cdc42 that have been reported to exert multiple cellular functions in osteoclasts, the most prominent of which includes regulating the dynamic actin cytoskeleton rearrangements. In addition, natural products and their molecular frameworks have a long tradition as valuable starting points for medicinal chemistry and drug discovery. Although currently, there are reports about the natural product, which could play a therapeutic role in bone loss dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…(2) CDC42 regulates the differentiation of the osteoclasts and osteoblasts, further maintain the function of bone modeling and remodeling. Thus, the downregulation of CDC42 might be correlated with the initiation of the AS 30‐33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) CDC42 regulates the differentiation of the osteoclasts and osteoblasts, further maintain the function of bone modeling and remodeling. Thus, the downregulation of CDC42 might be correlated with the initiation of the AS 30‐33 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the downregulation of CDC42 might be correlated with the initiation of the AS. 30 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Rac1 regulates cytoskeleton recombination, actin polymerization, and leading-edge extension by promoting actin assembly (17), which is necessary for the formation of lamellar lipid membranes and membrane folding (13). Without Rac1 and Rac2, the ability of osteoclasts to form actin cytoskeleton is insufficient (18).…”
Section: Rac1 Regulates Cell Adhesion Morphology and Movementmentioning
confidence: 99%
“…Cell division cycle 42 (CDC42), a member of the Rho GTPase family regulates cytoskeletal reorganization in various ways [32]. Although CDC42SE2 could not be validated in the current study, a previous study confirmed the importance of CDC42 in bone metabolism and bone deterioration [33,34]. In addition, CDC42 is closely correlated with immunity and inflammation [35].…”
Section: Proteasome Associated With Ho In Asmentioning
confidence: 63%